Dendrimeric nanosystem consistently circumvents heterogeneous drug response and resistance in pancreatic cancer. Issue 1 (27th August 2021) - Liu, Juan; Chen, Chao; Wei, Tuo; Gayet, Odile; Loncle, Céline; Borge, Laurence; Dusetti, Nelson; Ma, Xiaowei; Marson, Domenico; Laurini, Erik; Pricl, Sabrina; Gu, Zhongwei; et al.
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a deadly cancer with no efficacious treatment. The application of nanomedicine is expected to bring new hope to PDAC treatment. In this study, we report a novel supramolecular dendrimeric nanosystem carrying the anticancer drug doxorubicin, which demonstrated potent anticancer activity, markedly overcoming the heterogeneity of drug response and resistance of primary cultured tumor cells derived from PDAC patients. This dendrimer nanodrug was constructed with a fluorinated amphiphilic dendrimer, which self‐assembled into micelles nanostructure and encapsulated doxorubicin with high loading. Because of the fine nanosize, stable formulation and acid‐promoted drug release, this dendrimeric nanosystem effectively accumulated in tumor, with deep penetration in tumor tissue and rapid drug uptake/release profile in cells, ultimately resulting in potent anticancer activity and complete suppression of tumor growth in patient‐derived xenografts. Most importantly, this dendrimer nanodrug generated uniform and effective response when treating 35 primary pancreatic cancer cell lines issued from patient samples as a robust platform for preclinical drug efficacy testing. In addition, this dendrimer nanodrug formulation was devoid of adverse effects and showed excellent tolerability. Given all these uniquely advantageous features, this simple and convenient dendrimer nanodrug holds great promise as a potential candidate to treat the deadly PDAC. Abstract : A novel supramolecular dendrimeric nanosystem carrying the anticancer drug doxorubicin was developed in this study. We demonstrated this nanosystem markedly overcoming the heterogeneity of drug response and resistance of primary cultured tumor cells derived from 35 PDAC patients. This simple and convenient dendrimer nanodrug holds great promise as a potential candidate to treat the deadly PDAC.